2018
DOI: 10.1016/j.maturitas.2017.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among postmenopausal women enrolled in the Minnesota Green Tea Trial

Abstract: The findings of this descriptive analysis of postmenopausal women may help clinicians counsel women about expectations and treatment options to address menopause-associated symptoms and the relationship between postmenopausal symptoms and overall health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 15 publications
1
6
0
1
Order By: Relevance
“…This questionnaire was designed by Hilditch et al (29) at the University of Toronto in Canada and contains 29 items on menopausal symptoms and complications in four dimensions, including vasomotor, psychosocial, physical, and sexual, and the total score is obtained based on a Likert scale from 1 to 6. Lower scores indicate a better quality of life, and vice versa (30). The reliability of the Persian version of this scale has been confirmed in previous studies conducted on the quality of life in Iranian women with a Cronbach's alpha of 0.8 (9).…”
Section: The Menopause-specific Quality Of Life (Menqol) Questionnairesupporting
confidence: 68%
“…This questionnaire was designed by Hilditch et al (29) at the University of Toronto in Canada and contains 29 items on menopausal symptoms and complications in four dimensions, including vasomotor, psychosocial, physical, and sexual, and the total score is obtained based on a Likert scale from 1 to 6. Lower scores indicate a better quality of life, and vice versa (30). The reliability of the Persian version of this scale has been confirmed in previous studies conducted on the quality of life in Iranian women with a Cronbach's alpha of 0.8 (9).…”
Section: The Menopause-specific Quality Of Life (Menqol) Questionnairesupporting
confidence: 68%
“…To enhance the overall quality of life of women during transition to menopause and during post-menopausal period, it is important for the woman to know necessary information on what menopause is and how to deal with its related problems. Clinicians are recommended to interact with middle-aged women in order to give them advice on how to manage this crucial period of their lives [ 23 ]. This study aimed to evaluate the knowledge, attitudes and practices towards menopause among middle-aged Congolese women.…”
Section: Discussionmentioning
confidence: 99%
“…In general, menopausal women have been considered to suffer from cognitive disorders as a result of estrogen decline. However, this viewpoint was challenged by a recent study that demonstrated that women aged 50-54.9 years had even poorer memory than older women (39). Their verbal memory did decline at the menopausal transition but probably rebounded during the postmenopausal stage (40).…”
Section: Discussionmentioning
confidence: 99%